Pharmacological and toxicological assessment of innovative self-assembled polymeric micelles as powders for insulin pulmonary delivery. (September 2016) - Andrade, Fernanda; Fonte, Pedro; Costa, Ana; Reis, Cassilda Cunha; Nunes, Rute; Almeida, Andreia; Ferreira, Domingos; Oliva, Mireia; Sarmento, Bruno
Aim: Explore the use of polymeric micelles in the development of powders intended for pulmonary delivery of biopharmaceuticals, using insulin as a model protein.Materials & methods: Formulations were assessed in vitro for aerosolization properties and in vivo for efficacy and safety using a streptozotocin-induced diabetic rat model.Results: Powders presented good aerosolization properties like fine particle fraction superior to 40% and a mass median aerodynamic diameter inferior of 6 μm. Endotracheally instilled powders have shown a faster onset of action than subcutaneous administration of insulin at a dose of 10 IU/kg, with pharmacological availabilities up to 32.5% of those achieved by subcutaneous route. Additionally, micelles improved the hypoglycemic effect of insulin. Bronchoalveolar lavage screening for toxicity markers (e.g., lactate dehydrogenase, cytokines) revealed no signs of lung inflammation and cytotoxicity 14 days postadministration.Conclusion: Developed powders showed promising safety and efficacy characteristics for the systemic delivery of insulin by pulmonary administration.